Two FTD-ALS genes converge on the endosomal pathway to induce TDP-43 pathology and degeneration - Shao, Wei; Todd, Tiffany W.; Wu, Yanwei; Jones, Caroline Y.; Tong, Jimei; Jansen-West, Karen; Daughrity, Lillian M.; Park, Jinyoung; Koike, Yuka; Kurti, Aishe; Yue, Mei; Castanedes-Casey, Monica; et al. (Science (American Association for the Advancement of Science), 2022)
Frontotemporal dementia and amyotrophic lateral sclerosis (FTD-ALS) are associated with both a repeat expansion in the C9orf72 gene and mutations in the TANK-binding kinase 1 ( TBK1 ) gene. We found that TBK1 is phosphorylated in response to C9orf72 poly(Gly-Ala) [poly(GA)] aggregation and sequestered into inclusions, which leads to a loss of TBK1 activity and contributes to neurodegeneration. When we reduced TBK1 activity using a TBK1-R228H (Arg 228 →His) mutation in mice, poly(GA)-induced phenotypes were exacerbated. These phenotypes included an increase in TAR DNA binding protein 43 (TDP-43) pathology and the accumulation of defective endosomes in poly(GA)-positive neurons. Inhibiting the endosomal pathway induced TDP-43 aggregation, which highlights the importance of this pathway and TBK1 activity in pathogenesis. This interplay between C9orf72 , TBK1 , and TDP-43 connects three different facets of FTD-ALS into one coherent pathway. Frontotemporal dementia and amyotrophic lateral sclerosis share key genetics and pathology, but the connection between different known facets of their disease biology is not always clear. Shao et al . discovered an interplay between the disease-associated genes C9orf72 and TBK1 . Large repeats of glycine-alanine, which are produced by an expansion in C9orf72 , sequestered TBK1 into inclusions, inhibiting its function and impairing the downstream endosomal pathway (see the Perspective by Gallo and Edbauer). A mutation in TBK1 worsened these defects, enhancing disease phenotypes in mice. Remarkably, the disruption of the endosomal pathway also proved sufficient to induce the aggregation of TAR-DNA binding protein 43 (TDP-43), a key driver of degeneration in these diseases. —SMH Two frontotemporal dementia– and amyotrophic lateral sclerosis–associated mutations converge on the endosomal pathway during neurodegeneration.